2016
DOI: 10.1039/c6ra21348k
|View full text |Cite
|
Sign up to set email alerts
|

Solvent dependent isomerization of photochromic dithienylethenes: synthesis, photochromism, and self-assembly

Abstract: The self-assembly of photochromic dithienylethene molecules into circular nanostructures is reported. The formation of nanostructures is dependent on factors such as photoisomerization, solvent, and hydrogen bonding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Compared to the open isomer, the increased rigidity of the closed isomer might restrict the ring-shaped structure formation accompanied with stabilization by smaller self-assembly with size range 75-110 nm (Figure S19b). [60] The formation of the self-assembly can be correlated to several possible intermolecular interactions present in our system, such as: a) π-π interactions of NDI; [61] b) non-classical Hbonding of CÀ H of triazole unit. [62] The self-assembled behavior was further investigated with increasing percentage of water in THF solution.…”
Section: Photophysical Studiesmentioning
confidence: 92%
“…Compared to the open isomer, the increased rigidity of the closed isomer might restrict the ring-shaped structure formation accompanied with stabilization by smaller self-assembly with size range 75-110 nm (Figure S19b). [60] The formation of the self-assembly can be correlated to several possible intermolecular interactions present in our system, such as: a) π-π interactions of NDI; [61] b) non-classical Hbonding of CÀ H of triazole unit. [62] The self-assembled behavior was further investigated with increasing percentage of water in THF solution.…”
Section: Photophysical Studiesmentioning
confidence: 92%
“…DTE-containing multiphotochromic hybrids. [58][59][60] A multiphotochromic system reported by Feringa and coworkers illustrates the interesting utility of DTE for light-gated photochromism. [61] When a DTE unit is connected to an overcrowded alkene-based rotary motor via an ethynylene linkage, 6, operation of the motor becomes dependent on the isomerization state of the DTE (Figure 7).…”
Section: Multiphotochromic Systemsmentioning
confidence: 93%
“…Another DTE‐AZB hybrid, 4 , with ethynylene junctions, reported by Valiyaveettil et al, showed solvent‐dependent photochromic behavior. [ 59 ] Selective ring closure of the DTE core occurs upon irradiation at 365 nm in chloroform; at the same wavelength, concurrent DTE ring closure and E → Z photoisomerization of AZB proceed in THF. For both DTE‐AZB hybrids, selective maneuvering of the distinct chromophores is inefficient, and not all switchable states are addressable.…”
Section: Molecular Switches and Motors Activated By Multiple Orthomentioning
confidence: 99%
“…The conversion of 22 to 6a was performed using a modified procedure reported by Sen and Valiyaveettil. 15 Thus, bromide 22 was treated with 1.1 equiv of B 2 pin 2 in the presence of 5 mol% Pd(dppf)Cl 2 •CH 2 Cl 2 and 3.0 equiv of potassium acetate in 1,4-dioxane at 80 °C for 14 h to provide pinacol borate 6a in 84% yield. Cl 2 •CH 2 Cl 2 (5 mol%), B 2 pin 2 (1.1 equiv), KOAc (3.0 equiv), 1,4-dioxane, 80 °C, 14 h (84% 23a in 59% yield.…”
Section: Methodsmentioning
confidence: 99%
“…13 C NMR (126 MHz, CDCl 3 ): δ 28. 4, 56.4, 71.0, 80.3, 106.1, 111.2, 112.4, 127.5, 127.8, 128.5, 131.9, 136.9, 145.7, 148.5, 153. (15). Under an argon atmosphere, NBS (4.45 g, 25.0 mmol) was added portionwise to a solution of 14 (7.49 g, 22.7 mmol) in THF (140 mL) at −78 °C.…”
Section: -Benzyloxy-1-methoxy-4-nitrobenzene (12)mentioning
confidence: 99%